11° Conferência Estadual de Saúde do Maranhão: análise a partir da teoria da desdemocratização - MUNIZ, Ingrid Feitoza (2026)
Introduction: the Health Conferences are deliberative instances of Social Control of the Unified Health System institutionalized by Law n° 8142/1990. Every four years, civil society brings together to analyze public health and propose guidelines to compose health plans and policies. Despite their democratic potential, they face organizational and structural weaknesses both at the national and local levels, in a context of de-democratization of democratic institutions. In Maranhão, the 11th State Health Conference of Maranhão took place amid political polarization and budgetary dependence. The study analyzes its organization and challenges, contributing to the understanding of Social Control in the state of Maranhão. Objective: to analyze the organizational and structural context of the 11th State Health Conference of Maranhão. Methods: this is a qualitative research on the organization of the 11th State Health Conference of Maranhão. The study took place in São Luís – MA, from May 2023 to October 2025. The study population consists of the Organizing Committee and the Executive Committee of the conference, which totals 26 members, nine of whom participated in this study. As a research instrument, a semi-structured interview was prepared and data collection took place between June 2023 and August 2024. Content analysis of the interviews was carried out, according to the method of Bardin (2011), through the NVivo platform, resulting in three categories of analysis. The theoretical framework to support the analysis and discussion was Brown's Theory of Dedemocratization (2015). Results and Discussion: the interviews showed that the organization of the conference had weaknesses such as financial dependence, delays in resources, management failures and low leadership renewal, which limited autonomy and participatory effectiveness, reflecting the process of Dedemocratization described by Brown (2015). On the other hand, social mobilization, institutional partnerships, learning, integration and democratic exercise were highlighted as potentialities that strengthened the event. Finally, even in the face of structural and organizational challenges, the resistance of Social Control in the face of institutional dismantling and the advance of neoliberalism was evident. Final Considerations: despite the weaknesses and limitations of the conference in the midst of thecontext of Dedemocratization, the 11th State Health Conference of Maranhão reaffirmed the right to social participation in the management of health policies and evidenced the resistance of democratic institutions.